RealQual: Towards real-time high-resolution monitoring and prediction of water quality in estuaries and coastal areas - Final Report - Rodrigues, M. (2015)
This report presents the main activities and results of the project RealQual: Towards real-time highresolution monitoring and prediction of water quality in estuaries and coastal areas, a collaborative project of the FLAD / NSF 2013, Portugal - U.S. Research Networks Program. RealQual aimed at developing the foundations of a quality-controlled network for real-time, high-resolution monitoring and prediction of the water quality in estuaries and coastal areas. Regarding the real-time monitoring component, an online monitoring station for water quality was maintained operational in the Tagus estuary. Several procedures were tested for data quality control using the data from the SATURN OHSU-CMOP (Oregon Health & Science University – Center for Coastal Margin Observation and Prediction) network and will be extrapolated to the monitoring network of the Tagus estuary. The numerical modelling system for water quality ECO-SELFE was extended to improve its flexibility. A preliminary application of the coupled hydrodynamics and biogeochemical model was performed in the Tagus estuary, based on the improvements made to the horizontal grid and bathymetry. Tests to the computational times showed that the use of the biogeochemical model in real-time is possible and a set of requirements were established towards this deployment within the Water Information and Forecasting System (WIFF). A dedicated operational Web-based platform was developed for the project, providing access to the real-time data and forecasts of the hydrodynamics and fecal contamination in the Tagus estuary.